10 W CEP-stable few-cycle source at 2 µm with 100 kHz repetition rate - Neuhaus, M.; Fuest, H.; Seeger, M.; Schoetz, J.; Trubetskov, M.; Russbueldt, P.; Hoffmann, H. D.; Riedle, E.; Major, Zs.; Pervak, V.; Kling, Matthias F.; Wnuk, P. (Optics Express, 2018)
We developed a high repetition rate optical parametric chirped-pulse amplification (OPCPA) laser system based on fiber-laser-seeded Innoslab to generate few-cycle pulses around 2 µm with passively stable carrier-envelope phase (CEP) by difference frequency generation (DFG). Incorporating a piezo mirror before the DFG stage permits rapid CEP control. The OPCPA system is seeded by a stable supercontinuum generated in bulk material with the picosecond Innoslab pulses. Few-cycle pulses with durations of 17 fs and energies of over 100 μJ were produced in a single OPCPA stage. Three different nonlinear crystals: BBO, BiBO, and LNB were tested in the final parametric amplifier, and their average power related limitations are addressed.
CRIS-Team Scopus Importer:2023-04-20